Paediatric focal nodular hyperplasia: A case study of typical contrast-enhanced ultrasound findings with quantitative analysis and correlated with magnetic resonance imaging. (May 2021) - Panayiotou, Andreas; Rafailidis, Vasileios; Deganello, Annamaria; Sellars, Maria; Sidhu, Paul S
Introduction: Focal nodular hyperplasia, a benign liver tumour, is the second most common focal benign liver lesion, after a cavernous haemangioma. Contrast-enhanced ultrasound is used increasingly for the diagnostic work up and follow-up of focal liver lesions in adults, but is particularly valuable in the paediatric population, with the ability to reduce radiation and the nephrotoxic contrast agents used in computed tomography or magnetic resonance imaging. Confident recognition of focal nodular hyperplasia is important; it is benign, usually asymptomatic, of no clinical significance, of no clinical consequence or malignant potential. We present a case of focal nodular hyperplasia of the liver with its characteristic findings on conventional ultrasound, contrast-enhanced ultrasound with quantitative analysis and correlated with magnetic resonance imaging. Case presentation: A 15-year-old female with right upper quadrant abdominal pain was referred for liver ultrasound. A focal liver lesion was detected on B-mode ultrasound examination, and colour Doppler demonstrated no specific features. Contrast-enhanced ultrasound examination demonstrated early arterial enhancement, with a characteristic spoke-wheel pattern, centrifugal uniform filling of the lesion on the late arterial phase and sustained enhancement on the portal venous phase. Quantitative contrast-enhanced ultrasound has been performed, showing a typical curve of enhancement, as well as characteristic parametric images, supporting the interpretation of contrast-enhanced ultrasound and assisting the diagnosis. Magnetic resonance imaging demonstrated a central T2 hyperintense scar and similar enhancement characteristics as contrast-enhanced ultrasound on T1 gadolinium-enhanced sequences. Conclusion: Contrast-enhanced ultrasound is a useful technique for the differentiation of benign from malignant liver lesions and has the potential to establish the diagnosis of focal nodular hyperplasia, based on the enhancement pattern, which is similar to that observed on magnetic resonance imaging but can be better appreciated with superior temporal, contrast and spatial resolution of contrast-enhanced ultrasound.